Prospek Pembangunan Desa Bumi Harapan di Kecamatan Sepaku Pasca Ditetapkannya Ibu Kota Nusantara (IKN) di Kalimantan Timur - Indri Kencana Pramesti; Jumansyah, Jumansyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research aims to find out and identify potentials and analyze This research aims to find out and identify potential and analyze development prospects in Bumi Harapan Village after the establishment of the Archipelago Capital City (IKN). The main focus of research is on economic aspects, basic needs, infrastructure, and peaceful, just villages. This research also examines development challenges and strategies that can be implemented. The data collection method uses purposive sampling, which allows collecting relevant data from respondents selected based on certain criteria. The research results show that the prospects for economic development in Bumi Harapan Village are quite significant with the increase in investment and job opportunities arising from the establishment of IKN. Improvements in infrastructure, including transportation and communications, also show positive developments that can improve the quality of life of residents. Apart from that, efforts to create peaceful, just villages are starting to be implemented through various programs that support equality and social justice. However, this research also identified a major challenge in the form of lack of accessibility to basic needs such as clean water. Despite developing infrastructure and the economy, access to clean water is still a significant problem for local residents. This research recommends the development of a more efficient water distribution system and the construction of adequate water storage facilities.